Subtypes of masked hypertension and target organ damage in untreated outpatients - Dong-Yan Zhang; Yi-Bang Cheng; Qian-Hui Guo; Ying Wang; Chang-Sheng Sheng; Qi-Fang Huang; De-Wei An; Ming-Xuan Li; Jian-Feng Huang; Ting-Yan Xu; Ji-Guang Wang; Yan Li (Blood Pressure, 2020)
Purpose: Masked hypertension (MHT) is characterised as an office normotension in the presence of out-of-office hypertension, and can be further categorised as isolated daytime (dMHT), night-time (nMHT) or day-night MHT (dnMHT) according to the time when hypertension is present. MHT is associated with adverse cardiovascular outcome. However, no previous studies contrasted these MHT subtypes in their associations with target organ damage (TOD). Materials and methods: Consecutive untreated patients referred for ambulatory blood pressure (BP) monitoring to our Hypertension Clinic were recruited. Office and ambulatory BPs were measured using the Omron 7051 and SpaceLabs 90217 monitors, respectively. The BP thresholds of daytime and night-time hypertension were of ≥135/85 mmHg and ≥120/70 mmHg, respectively. We performed various TOD measurements, including carotid-femoral pulse wave velocity (cfPWV), carotid intima-media thickness (cIMT), left ventricular mass index (LVMI) and E/E’, estimated glomerular filtration rate (eGFR) and urinary albumin-to-creatinine ratio (UACR). Results: The 1808 participants (mean age, 51 years; women, 52%) included 672 (37.2%) MHT subjects, among whom 123 (18.3%) had dMHT, 78 (11.6%) nMHT, and 471 (70.1%) dnMHT. In all participants as well as patients with office normotension (n = 1222), ambulatory daytime and night-time BPs were similarly associated with all TOD measurements (p ≥ 0.20) after multivariate adjustment. Compared to normotensive subjects (p < 0.05), patients with dMHT had faster cfPWV (7.81 vs. 7.58 m/s) and thicker cIMT (637.6 vs. 610.4 µm), patients with nMHT had thicker cIMT (641.8 vs. 610.4 µm) and increased UACR (0.79 vs. 0.59 mg/mmol), and patients with dnMHT had all worse TOD measures mentioned-above plus elevated eGFR (120.7 vs. 116.8 ml/min/1.73m2). Conclusion: MHT was associated with TOD irrespective of subtype, although TOD varied slightly across these subtypes. The study highlights the importance of controlling both daytime and night-time BP in hypertensive patients.